Respostas
respondido por:
1
Resposta:
Explicação passo a passo:
Equação de primeiro grau
A) -16 - x = 2x + 11
-x - 2x = 11 + 16
- 3x = 27 (-1)
3x = -27
x= -27/3
x= -9
B) 3x-17= 13
3x= 13-17
3x= -4
x=-4/3
C) x +x -x =23
2x- x = 23
x= 23
D) -12 - 24 = -3x
-36 = -3x (-1)
36 = 3x
3x = 36
x=36/3
x=12
Espero ter ajudado!!!!
respondido por:
0
Resposta:
a) = -9 b) = 10 c) = 23 d) =12
Explicação passo a passo:
-16-x=2x+11
-x-2x=11+16
-3x=27
x=-27/3
x=-9
3x-17=13
3x=13+17
x=30/3
x=10
x+x-x=23 x+x=2x 2x-x=x
x=23
-12-24=-3x
-36=-3x
-36/-3=x
36/3=x
12=x
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás